A Compact Pixel Circuit for Externally Compensated AMOLED Displays - Hing-Mo Lam (IEEE, 2018)
Nonuniformity and aging are two major issues with the pixel circuits of active-matrix organic light-emitting diode displays. External compensation scheme is typically employed to mitigate these two issues, since various off-panel resources, such as on-chip processors and memory arrays, can be utilized. A new pixel circuit with feedback path for the external compensation scheme is proposed in this paper. The data line and monitor line are shared for two adjacent columns of pixel circuits to increase the aperture opening ratio of display panel. The number of thin-film transistors attached to each data line is reduced by 50% with the proposed pixel circuit compared to the traditional pixel circuit. The average power consumption of the normal display operation is thereby reduced by 15%.